Sustainable Fabrication of Green Chemistry Silica-Carbon Composites Derived from Coconut Coir and Dicalite Using Ion Exchange Method - Lely Amoi; Adinda Dwi Febriana; Srie Muljani; Suprihatin; Nurul Widji Triana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This research aimed to synthesise sustainable silica–carbon composites derived from coconut coir and dicalite diatomite using an ion-exchange-assisted sol–gel method and to evaluate the effects of gel-forming pH and carbonisation temperature on the resulting composite characteristics. The investigated parameters included gel formation pH 5 and carbonization temperature (400–800 °C). FTIR, XRD, and SEM–EDX analyses were applied to determine functional groups, phase structure, elemental composition, and surface morphology. The results revealed that the composite synthesised at pH 5 and carbonised at 800 °C exhibited the optimal structural properties. This condition produced a homogeneous morphology, balanced silica–carbon integration, reduced sodium residue, and a stable amorphous phase without crystalline formation. Higher carbonization temperatures enhanced siloxane network condensation and improved interfacial bonding between silica and carbon phases. The synthesis guidelines for silica-carbon composite fabrication should therefore emphasise controlled acidic gel formation and high-temperature carbonisation to produce structurally stable, well-integrated materials suitable for adsorption and environmental applications. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 9: Industry, Innovation and Infrastructure